Does there exist an optimal budget balance to improve economic growth? empirical evidence from Asian countries - Oanh Kim Thi Tran (Cogent Economics & Finance, 2022)
Using panel data regression of 48 countries during 2000-2019, the research aims to examine the role of budget balance on economic growth in Asia. Also, with the application of Panel Threshold Regression (PTR), the author tests the nonlinear relationship and to identify an optimal budget balance threshold to achieve the most effective economic growth. The study shows that the lower national budget deficit level is remained, the greater economic growth in Asia is driven. Additionally, it is revealed that an effective economic growth is best promoted with budget balance ranging from 22.6935% GDP to 25.1950% GDP. However, only a few of nations in the sample have achieved the optimal threshold of budget balance above during the period of research. Meanwhile, several countries in Asia have been suffering from the budget deficit for many years. Therefore, in order to stabilize the economic development, most of the Asian countries should adjust the national budget revenue and expenditure process to keep the balance properly.
Keywords: B23; C24; H61; O47; 330; Budget balance; economic growth; threshold regression; nonlinear relationship; Asian countries